Measurement and monitoring of overhead transmission line sag in smart grid: A review - Ayman Uddin Mahin (Wiley, 2022)
Abstract In a transmission line, sag is intentionally provided to relax the tension on the wire when placed between two terminals. However, thermal stress and extreme weather conditions can cause increases in transmission line sag, which can eventually damage transmission line infrastructure. In this regard, this paper examines a number of sag measurement techniques based on physical or optical properties and integrated with signal processing and communication technologies. The performance of different sag measurement methods is compared in terms of accuracy, precision and key feature. Several challenges and limitations of the existing sag measurement mechanisms are reported. A number of recommendations to address the identified challenges are made. Moreover, an efficient communication framework for sag related information exchange is proposed. This comprehensive review of the sag measurement techniques will facilitate the evolution of new and efficient real‐time sag measurement and monitoring methods.